Chińczycy w Etiopii? „Seres” w „Opowieść etiopskiej o Teagenesie i Chariklei” Heliodora - Malinowski , Gościwit (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
In the Ethiopian adventures of Theagenes and the Chariclea by Heliodorus, Seres are mentioned twice as allies of the Ethiopian king in the battle against the Persians (9, 16–18) and participants in the royal audience at Meroe (10, 25–26). They donate silk produced in their country to the King Hydaspes, so they are usually considered Chinese by commentators. However, the world presented in Heliodorus’ novel is set in the realities of the Roman era and Roman eastern trade, when African countries also participated in trans-oceanic contacts with India. The archetype of the Heliodorus’ Seres can be found in the kingdom of Chera, located in southern India.